The root apoplastic pH as an integrator of plant signaling - Gámez-Arjona, Francisco M.; Sánchez-Rodríguez, Clara; Montesinos, Juan Carlos (Frontiers in Plant Science, 2022)
Plant nutrition, growth, and response to environmental stress are pH-dependent processes that are regulated at the subcellular level. The root apoplastic pH is especially sensitive to external cues and can also be modified by intracellular inputs, such as hormonal signalling. An optimal crosstalk of the mechanisms involved in the extent and span of the apoplast pH fluctuations promotes plant resilience to detrimental biotic and abiotic circumstances. The fact that variations in local pHs are a standard mechanism in different signalling pathways indicates that the pH itself can be the pivotal element to provide a physiological context to plant cells regions, allowing a proportional reaction to different situations. This review brings a collective vision of the causes that initiate root apoplastic pHs variations, their interaction, and how they influence root response outcomes.